Pentingnya Komunikasi Verbal Dalam Proses Pembelajaran (Kajian Perspektif Komunikasi Efektif Pada Pembelajaran) - Nita Novita (MANAJEMEN INFORMATIKA, 2010)
The learning process is an activity that is very meaningful activity for lecturers and students. In the process of learning, lecturers communicate in a way speaks for delivering course material to students. Communication is done can be verbal and nonverbal communication. But that is discussed in this articles, verbal communication is usually used by lecturers and students, when interacting in the learning in the classroom (classroom and laboratory space). Verbal communication plays a role in the learning process, when the lecturer delivering course material and students to respond to the lesson material it receives. This article aims to explain the importance of verbal communication in the learning process, explaining that oral communication can be done in an effective way to communicate and explain the role of faculty in developing effective communication. This article is a review of interpersonal communication materials that verbal communication is necessary in the process of learning in the classroom, both in the classroom or computer lab space. The studies in this article are based on a review of empirical and review literature from several authors about verbal communication. Conclusion that verbal communication plays an important role in helping improve the effectiveness of learning in lecture halls, can achieve learning goals by applying effective communication, and lecturers very important role in building effective communication.